2021
DOI: 10.3390/math9090986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Game-Based Learning in Mathematics Education on Students’ Affective Domain: A Systematic Review

Abstract: In modern education nowadays, the use of game-based learning as a teaching and learning method is popular in all school subjects, including mathematics. There are numerous studies dealing with the influences of this teaching method on the students’ achievements. Modern teaching theories consider an important effect of education on the development of students’ affective domain, connected with the subject and its teaching. In this work, the author studies journal articles that the use game-based learning in math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 78 publications
2
12
0
1
Order By: Relevance
“…Game-based learning affects knowledge gains in addition to mathematical accomplishments. However, affective factors like the students' attitudes and beliefs about mathematics and its teaching are also crucial components of mathematics education because they can have a significant impact on the students' mathematical abilities and future mathematic learning (Vankúš, 2021 ). Attitude toward mathematics is defined as a liking or disliking of mathematics, a tendency to engage in or avoid mathematics activities, a belief that one is good or bad at mathematics and a belief that mathematics is useful or useless (Kurniasih et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Game-based learning affects knowledge gains in addition to mathematical accomplishments. However, affective factors like the students' attitudes and beliefs about mathematics and its teaching are also crucial components of mathematics education because they can have a significant impact on the students' mathematical abilities and future mathematic learning (Vankúš, 2021 ). Attitude toward mathematics is defined as a liking or disliking of mathematics, a tendency to engage in or avoid mathematics activities, a belief that one is good or bad at mathematics and a belief that mathematics is useful or useless (Kurniasih et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of further research, namely, games that are integrated into learning tools can improve elementary school student learning outcomes obtained through increasing experimental group posttest learning outcomes (Nand et al, 2019). There is a positive effect of game-based learning on students' learning motivation, involvement, and attitudes, which is 84% (Vankúš, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Gamebased learning and teaching uses the motivation and competition that naturally arise in play to achieve the goals and outcomes of teaching. There are numerous studies showing many positive effects of such learning (Ku et al (2014), Vankúš (2021) and although some of the articles report mixed results, none report a negative impact. An extensive literature review of serious games based on multiple criteria (Backlund and Hendrix (2013)) found an overwhelming amount of evidence that serious games have a positive impact on learning and motivation.…”
Section: Game-based Teaching and Learningmentioning
confidence: 99%